The trial of democracy : black suffrage and northern Republicans, 1860-1910 - Wang, Xi, 1955- (Studies in the legal history of the South., 1997)
Following the Civil War, Republicans teamed with activist African Americans to protect Black voting rights through constitutional reform. This work looks at the forces and mechanisms which led to Black suffrage, and follows the issues into the early 20th century.